The future of employment: How Generation Z is reshaping entrepreneurship through education? - Aulia Istiana Hidayat (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2024)
The evolving landscape of work is increasingly shaped by Generation Z, a cohort characterized by its digital fluency, innovative mindset, and entrepreneurial spirit. This study explores how Gen Z is redefining entrepreneurship and the implications for the future of work. The primary aim of this research is to understand the unique entrepreneurial tendencies of Gen Z and how these tendencies influence business practices, workplace culture, and economic development. The research adopts a literature review approach, analyzing existing studies, articles, and reports on Gen Z's entrepreneurial behaviors, motivations, and challenges. Sources include academic journals, industry reports, and reputable media publications that provide insights into the characteristics and trends of Gen Z entrepreneurs. The findings indicate that Gen Z entrepreneurs are driven by a strong desire for independence, social impact, and technological innovation. They tend to leverage digital tools and social media to create and scale businesses rapidly. Moreover, their approach to entrepreneurship is more inclusive and collaborative, often focusing on sustainable and ethical business practices. This study concludes that Gen Z's redefinition of entrepreneurship will likely lead to significant changes in the future of work, emphasizing flexibility, digital integration, and value-driven business models